Effect of the Passive Stabilizer Bar on the Vehicle's Stability. (12th May 2022) - Nguyen, Duc Ngoc; Dang, Ngoc Duyen; Tran, Thi Thu Huong; Hoang, Thang Binh; Nguyen, Tuan Anh
Abstract : The phenomenon of vehicle rollover usually occurs when the driver suddenly steers at high speed. The centrifugal force will appear and cause the vehicle's body to tilt. To overcome this situation, the solution of using the stabilizer bar is proposed. The passive stabilizer bar has a simple structure, low cost, and long service life. As a result, it is now a standard on most vehicles. This paper has established a dynamic model to describe a vehicle's oscillation. As a result of the study, the maximum roll angle of the vehicle was reduced from 9.0° to 8.2° when the stabilizer bar was used. Besides, the minimum value of the vertical force at the wheel reached 485(N) and 1162(N), respectively, corresponding to the two survey cases. The movement trajectory of the vehicle when using the stabilizer bar does not have a big difference compared to the case when the vehicle does not use the stabilizer bar. So, the vehicle's stability and safety can be effectively improved. This is the basis for further developing complex stable bar patterns in the future.